C5 nerve root palsy after posterior cervical spine surgery: A review of the literature. (7th February 2017) - Pan, Fu-Min; Wang, Shan-Jin; Ma, Bin; Wu, De-Sheng
Background: C5 palsy is a serious complication after cervical decompression surgery in which the patient shows a deterioration in power of the deltoid or biceps brachii by at least one grade in the manual muscle test without aggravation of lower extremity function. Although there are several hypotheses regarding the etiology of C5 palsy, the pathogenesis and preventive measures remain unidentified and many other controversies remain. Objective: To systematically review the clinical features, risk factors, mechanism, and preventive measures of C5 palsy after posterior cervical decompression surgery. Materials and methods: PubMed was searched to identify eligible studies that contained more than 10 cases and focused on C5 palsy. Microsoft Excel was used to analyze the data. Statistical comparisons were made when appropriate. Results: Out of 718 papers involving C5 palsy, 28 met the inclusion criteria. The average incidence rate was 7.8% (range, 1.4–23.0%). Risk factors for C5 palsy included age, male gender, ossification of the posterior longitudinal ligament, and stenosis of the C4–C5 intervertebral foramen. C5 palsy occurred from immediately to 2 months after surgery, and recovery time ranged from 48 h to 41 months. Hypotheses for the mechanism of C5 palsy included root involvement and spinal cord impairment. Foraminotomy and intraoperative neuromonitoring were the two main methods used to prevent C5 palsy. Conclusion: C5 palsy is a serious complication occurring at the early stage after cervical decompression surgery. Foraminotomy and intraoperative neuromonitoring were the two main methods to prevent C5 palsy. The incidence of C5 palsy is low, but it can place a serious burden on the patients' quality of life and finances. The risk factors and mechanism of C5 palsy are still controversial. However, under conservative therapy, the prognosis is usually good. Higher quality studies are necessary for drawing more reliable and convincing conclusions about this disease.